Pneumatosis Cystoides Intestinalis: An Unusual Cause of Intestinal Ischemia and Pneumoperitoneum - Ogul, Hayri (Int Surg, 2015)
Pneumatosis cystoides intestinalis (PCI), with an unknown etiology, is an uncommon disease characterized by the presence of multiple gas-filled cysts within the submucosa or subserosa of the intestinal wall. Intestinal obstruction and/or perforation are relatively uncommon complications associated with PCI. The patients are often prone to misdiagnosis or mistreatment. The diagnosis of PCI is based on plain radiography or endoscopy. Multidetector computed tomography (MDCT) provides data on other intra-abdominal pathologies. Therefore, it is an important modality for the diagnosis of PCI. We present a case of PCI in a 58-year-old man affected by peritoneal free air with multidetector computed tomography imaging findings. We performed the plain film of the abdomen, and MDCT studies that showed numerous, diffuse, bubble-like intramural gas collections into the jejunum, ileum, and colon walls at the left-upper quadrant of the abdomen. MDCT findings were confirmed by surgical exploration.